"I passed the test!" Evidence of diagnostic misconception in the recruitment of population controls for an H3Africa genomic study in Cape Town, South Africa. Issue 1 (December 2017) - Masiye, Francis; Mayosi, Bongani; de Vries, Jantina
Abstract Background Advances in genetic and genomic research have introduced challenges in obtaining informed consent for research in low and middle-income settings. However, there are only few studies that have explored challenges in obtaining informed consent in genetic and genomic research in Africa and none in South Africa. To start filling this gap, we conducted an empirical study to investigate the efficacy of informed consent procedures for an H3Africa genomic study on Rheumatic Heart Disease (RHDGen) at the University of Cape Town in South Africa. The main aim of the study was to understand ethical challenges in obtaining informed consent in the RHDGen study. Methods We used a qualitative study methodology involving in-depth interviews and participant observations. Our study participants were RHDGen cases (patients), healthy controls and research staff involved in the recruitment of RHDGen cases and controls. In total, we conducted 32 in-depth interviews with RHDGen cases and controls, 2 in-depth interviews with research staff and 57 direct observations of the consent procedures of RHDGen cases and controls. The interviews were conducted in English, audio-recorded and transcribed verbatim. Data were analyzed using thematic content analysis. The study was conducted in 3 sites within Cape Town, South Africa. Results Most healthy controls joined the RHDGen study in order to be screened for rheumatic heart disease (diagnostic misconception). A majority of RHDGen cases decided to join the RHDGen study because of therapeutic misconception. Conclusion The ethical challenges that impacted on obtaining informed consent in the RHDGen study were complex. In this study, the main challenges were diagnostic misconception among RHDGen controls and therapeutic misconception among RHDGen cases.